Sex- and age-specific differences in excess mortality in China during the COVID-19 pandemic: a study based on official vital statistics data - Li, Yao (Frontiers in Epidemiology, 2025)
IntroductionThis study aimed to investigate the excess mortality observed in China between 2020 and 2023 and its underlying causes, including the COVID-19 pandemic, sex ratio, and aging trends.MethodsWe collected data regarding number of deaths and mortality rates of the years 2015–2019 from the China Statistical Yearbook of Population and Employment, and analyzed the data by age and sex. We created a standardized sex and age structure dataset and compared the excess mortality rates of different sexes and age groups for the years 2020 to 2023.ResultsThe sex-and age-specific number of deaths in all three years decreased compared to the number of deaths in the standardized sex and age structure dataset. The most significant decline was observed in 2021, whereas the number of deaths in 2022 and 2023 increased compared to that in 2021. It has been found that excess mortality is generally less prevalent among older age groups, and excess mortality rate tends to be lower among younger age groups. Additionally, in 2021, 2022, and 2023, the excess mortality rate was greater for men than for women, whereas it was greater for women in 2020. These differences can be attributed to various factors.DiscussionThis is the first study to examine excess mortality in China during the COVID-19 pandemic using age- and sex-standardized data. These findings underscore the need for a deeper exploration of the effects of sex and age on health outcomes.